A multi-objective emergency vehicle scheduling optimisation model. (7th December 2020) - Yao, Jiao; Shao, Chuwei; Xia, Xiaomei; Wang, Pincheng; Wei, Yu; Wang, Jin
Various types of emergencies incidents occur frequently, which may cause casualties and huge economic losses. How to optimise the scheduling of emergency rescue vehicles and improve their rescue efficiency is of great significance. Based on the analysis of its influencing factors the emergency vehicle scheduling optimisation model was firstly established, which was oriented to achieve three objects, minimising total travel time, total cost of dispatching travel, and maximising the path reliability. Moreover, the model was solved by Non-dominated Sorting Genetic Algorithm with elite strategy (NSGA-II algorithm). Finally, the local road network in Huangpu District, Shanghai, China was taken as to verify the model in this study. The results show that the optimal solution of the model can achieve the optimal total travel time, and total travel cost and path reliability of the scheduling scheme can also satisfy requirements, which means good validity and practicability.